The Principle of Justice Administered Only by the Court When Making a Pre-Trial Cooperation Agreement and Special Trial Order - A. A. Suvorova (Сибирское юридическое обозрение, 2015)
The article investigates the problems of realization of the principle of justice administered only by the court in special conditions of judicial proceedings, suggests the ways of optimizing the procedure of making a pre-trial cooperation agreement.